2012
DOI: 10.1097/cad.0b013e32834b85e8
|View full text |Cite
|
Sign up to set email alerts
|

Antimetastatic activity isolated from Colocasia esculenta (taro)

Abstract: Breast cancer mortality is primarily due to the occurrence of metastatic disease. We have identified a novel potential therapeutic agent derived from an edible root of the plant Colocasia esculenta, commonly known as taro, that has demonstrable activity in a preclinical model of metastatic breast cancer and that should have minimal toxicity. We have shown for the first time that a water-soluble extract of taro (TE) potently inhibits lung colonizing ability as well as spontaneous metastasis from mammary gland-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
60
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 20 publications
(22 reference statements)
2
60
0
Order By: Relevance
“…suggests that it may possess anti-inflammatory, anemiagenic, antialopecic, anti-leucotriene-D4, immunostimulatory properties and also provides a biochemical rationale for the inhibition of breast and prostate cancer cell lines demonstrated by C. esculenta as reported by Kundu et al (2012) and for the hypocholesterolemic actions also demonstrated by C. esculenta as reported by Eleazu et al (2016). 9,12-Octadecadienoyl chloride, a linoleoyl chloride that constituted 0.77% of the extract was reported to possess antisecretory, choleretic, contraceptive, antispermatogenic and antitubercular properties (Kalaivani et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…suggests that it may possess anti-inflammatory, anemiagenic, antialopecic, anti-leucotriene-D4, immunostimulatory properties and also provides a biochemical rationale for the inhibition of breast and prostate cancer cell lines demonstrated by C. esculenta as reported by Kundu et al (2012) and for the hypocholesterolemic actions also demonstrated by C. esculenta as reported by Eleazu et al (2016). 9,12-Octadecadienoyl chloride, a linoleoyl chloride that constituted 0.77% of the extract was reported to possess antisecretory, choleretic, contraceptive, antispermatogenic and antitubercular properties (Kalaivani et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Kundu et al (2012) reported in their studies that water soluble extract of C. esculenta demonstrated antimestatic activity by inhibiting the proliferation of some breast and prostate cancer cell lines. Their study further showed that tumour cell migration was completely blocked by the C. esculanta extract.…”
Section: Discussionmentioning
confidence: 99%
“…3 Another lectin-like protein from taros was reported to inhibit prostaglandin E2 synthesis, down-regulate cyclooxygenase 1 and 2 mRNA expression, potently inhibit lung-colonizing ability and spontaneous metastasis of mammary tumors. 25 Here, our results showed that taro lectin (Accession number: A5HMM7) can bind to surface receptors of DRG cells and alters the intracellular free calcium which may further induce itch or pain.…”
mentioning
confidence: 87%
“…It is nutritionally superior to yam and cassava in terms of its digestibility, contents of crude protein and essential minerals, such as Ca, Mg, and P (Chukwu, 2012). All parts of the cocoyam (corm, cornel, leave and flower) are edible and it is used in the treatment of diabetes, prevention of cancer and as food for the aged people, individuals and children (Kundu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%